PENGARUH LINGKUNGAN KERJA DAN KOMITMEN KERJA TERHADAP KINERJA GURU DI SMP NEGERI 4 KOTA PROBOLINGGO - jurnalpps pps; Windawati Suudiyah (Prodi Magister Manajemen Universitas Wijaya Putra, 2021)
This study is rto determine the effect of the work environment and work commitments on the performance of teachers of SMP Negeri 4 Probolinggo. The respondents of this study were 35 public junior high school teachers in Probolinggo City. Using saturated sampling techniques because the number of respondents under 100. Analysis of the data used in this study are: multiple linear regression analysis, t test (partial) and F test (simultaneous) aims to determine and analyze the effect of the work environment and work commitment on the performance of teachers of SMP Negeri 4 Probolinggo. This type of research is explanatory research with a research approach using a quantitative approach supplemented by descriptive methods. The results showed that the work environment and work commitment had a positive and significant influence on the performance of teachers of SMP Negeri 4 Probolinggo. Keywords: work environment, work commitment, performance